Faktor Anteseden Penerapan E-Filling pada Masa Pandemi COVID-19 - Budiraharjo, Dadang Eko; Orbaningsih, Dwi (SKeTsa Bisnis (e-jurnal), 2022)
The purpose of this study is to analyze the effect of income on taxpayer behavior and individual taxpayer compliance, e-filing policy on taxpayer behavior and individual taxpayer compliance, taxpayer behavior on individual taxpayer compliance, income and e-filing policies towards individual taxpayer compliance. individual taxpayer compliance through taxpayer behavior. The research method used is PLS on 91 taxpayer respondents at the North Malang Primary Tax Office by using accidental sampling. The results show that the effect of income on taxpayer behavior is negative and insignificant, e-filing policy on taxpayer behavior is positive and insignificant, taxpayer behavior towards personal taxpayer compliance is negative and significant, income on personal taxpayer compliance is positive. and significantly, e-filing policy on personal taxpayer compliance is positive and significant, income and e-filing policy on personal taxpayer compliance through taxpayer behavior has a significant effect.